Kinetic analysis of thermal degradation of NR/EPDM blends with maleic anhydride as compatibilizer: The eï¬ect of the reactive accelerators - Mayasari, Hesty Eka; Yuniari, Arum (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 2017)
Thermal characteristic is important to determine the thermal resistance of a polymer. In this work, the thermal characteristics of the NR/EPDM blends was investigated to study the storage and application condition of the blends. The NR/EPDM blends were prepared in the two-roll mill by using MAH as a compatibilizer with several types of accelerators, i.e., MBTS from thiazole group, the combination of MBTS and TMTD from thiuram group, and TBBS from sulphenamide group. This research used the thermogravimetric method with the heating rate of 10, 15, and 20ºC/min. The kinetic parameters are calculated by using Coats-Redfern equation. The degradation of NR/EPDM blends occurs in two stages (frst stage at 220-420ºC and second stage at 420-520ºC). Combination of MBTS and TMTD give higher energy activation (112.236 kJ/mol), followed by MBTS-blend (111.999 kJ/mol), and TBBS-blend (110.856 kJ/mol). Combination of MBTS and TMTD accelerator with MAH as the compatibilizer is the proper choice for NR/EPDM blends to get a good thermal stability.